Estudio de los sistemas para la administración de la distribución DMS y de los requerimientos para su implementación - Chiluisa Velasco, Kleber Fabián (2011)
The primary objective for the development of this study, entitled “STUDY FOR SYSTEM OF THE ADMINISTRATION OF THE DISTRIBUTION DMS AND REQUIREMENTS FOR IMPLEMENTATION" search to present the main requirements for the implementation of the DMS, that will be analyzed under two approaches: • First, look for interoperability between systems in utilities, using the Common Information Model (CIM). • Second, to model the main processes for the operation and planning of the distribution network, which take place in a power distribution utility, and which will be supported by the DMS.